1992
DOI: 10.1007/bf02636106
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant properties of individual phospholipids in a salmon oil model system

Abstract: The antioxidant properties of phosphoHpids (PL) in a refined salmon oil model system were measured by deteP mining changes in the 2-thiobarbituric acid number and decreases in the ratio of docosahexaenoic acid (DHA)I palmitic acid (22:6/16:0) of a fish oil system incubated at 180°C for up to 3 h. The more phosphatidylcholine (PC) added to the oil system, the higher the oxidative stability obtained. The order of effectiveness of commercial phospholipids in inhibiting oxidation and the loss of polyunsaturated fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(77 citation statements)
references
References 14 publications
3
73
0
Order By: Relevance
“…Non-stripped BO and emulsion were more stable than non-stripped EPO and emulsion due to the presence of much higher amounts of tocopherols and phospholipids, phosphatidylcholine (PC) and phosphatidylethanolamine (PE). PC and PE were both previously shown to be effective antioxidants in edible oils [29].…”
Section: Stability Of Bo and Epomentioning
confidence: 98%
“…Non-stripped BO and emulsion were more stable than non-stripped EPO and emulsion due to the presence of much higher amounts of tocopherols and phospholipids, phosphatidylcholine (PC) and phosphatidylethanolamine (PE). PC and PE were both previously shown to be effective antioxidants in edible oils [29].…”
Section: Stability Of Bo and Epomentioning
confidence: 98%
“…Choline and ethanolamine which are degradation products of PC and PE, respectively, decreased the autoxidation of herring oil at 40 1C (Saito & Ishihara, 1997). PC improved the oxidative stability of salmon oil during heating at 180 1C for 3 h (King, Boyd, & Sheldon, 1992 oxidation of trilinolein at 37 1C (Ohshima, Fujita, & Koizumi, 1993).…”
Section: Introductionmentioning
confidence: 96%
“…King, Boyd, and Sheldon (1992) reported that egg yolk phospholipids exhibit antioxidant activity in a refined salmon oil model system, and also demonstrated that the presence of nitrogen improved the antioxidant activity of phospholipids [104]. The antioxidant activity was positively associated with the degree of fatty acid unsaturation [81].…”
Section: Phospholipidsmentioning
confidence: 99%